Pediatric Critical Care Medicine Training in India: Past, Present, and Future - Bhalala, Utpal; Khilnani, Praveen (Frontiers in Pediatrics, 2018)
Pediatric critical care services in India have grown with leaps and bounds. There has been a growing need of physicians specially trained in pediatric critical care medicine (PCCM) in India. Physicians returning to India after their formal training in PCCM abroad have partly supported this growing need. Development of formal PCCM training programs in India has been a huge step toward supporting the growing clinical needs. This article focuses on advances in pediatric critical care training in India and its future directions.